2021
DOI: 10.1155/2021/2887302
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of English Listening Teaching Based on a Wireless Communication Microprocessor and Virtual Environment

Abstract: This paper presents an in-depth analysis and research on teaching English listening through a wireless communication microprocessor combined with a virtual environment and designs and implements an English listening teaching experiment. Based on an in-depth understanding of wireless communication algorithms, this thesis extends the instruction set based on the general-purpose compact instruction set computer architecture (RISC) for common operations in wireless communication algorithms, adding new instructions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The data that support the findings of this study are openly available at https://www.hindawi.com/journals/js/2021/ 2887302/ [doi:10.1155/2021/2887302], reference number [13].…”
Section: Data Availabilitysupporting
confidence: 71%
See 1 more Smart Citation
“…The data that support the findings of this study are openly available at https://www.hindawi.com/journals/js/2021/ 2887302/ [doi:10.1155/2021/2887302], reference number [13].…”
Section: Data Availabilitysupporting
confidence: 71%
“…For example, Bakhsh developed a set of learning materials to help students learn Chinese phonetic symbols and applied them in a specific kindergarten classroom to explore whether they could facilitate the learning of preschoolers compared with traditional paper-based teaching resources [ 12 ]. Liu applied augmented reality to their students' learning of fables, providing them with 3D models, audio, and related interactive props, and found that their students' interest in learning was greatly enhanced [ 13 ].…”
Section: Related Workmentioning
confidence: 99%
“…Liu [9] employed various tools and approaches in the virtual classroom, including video conferencing systems [9], and a multimedia environment that incorporates a whiteboard and text chat, among others. The students are accessible to many types of learning and teaching resources, including e-mail, YouTube, and wikis, while others make use of learning management systems (LMS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From virtual reality classrooms to virtual reallity labs and from virtual reality immersive theaters to virtual reality house viewing, virtual reality technology has entered the lives of ordinary people. Everyone is inevitably in contact with the new technology, constantly learning to use it through learning and thus forming physical habits [3]. In the interaction with virtual reality technology objects, the technology objects make the body believe that it is in the real space; the immersive character of virtual reality technology, coupled with the interactive and multisensory character, makes the audience mobilize the body perception to interact with the technology objects and then create the illusion of being in the real space.…”
Section: Virtual Reality Technologymentioning
confidence: 99%
“…In the interaction with virtual reality technology objects, the technology objects make the body believe that it is in the real space; the immersive character of virtual reality technology, coupled with the interactive and multisensory character, makes the audience mobilize the body perception to interact with the technology objects and then create the illusion of being in the real space. The advancement of human history is inextricably linked to the development of technology [3].…”
Section: Virtual Reality Technologymentioning
confidence: 99%